Sexual Dimorphism in Body Size and Wing Loading for Three Cicada Species. (28th April 2022) - Shi, Peijian; Jiao, Yabing; Niklas, Karl J; Li, Yirong; Guo, Xuchen; Yu, Kexin; Chen, Long; Hurd, Lawrence E
Abstract: Sexual dimorphism in body size has been observed for many insect species. However, whether dimorphism influences the flight performance for closely related insects or between the genders of conspecifics has seldom been examined. Wing loading (i.e., body mass/total wing area, WL = M/A ) is an important indicator of flight efficiency and maneuverability. We examined the potential for sexual dimorphism and interspecific differences in wing loading for three cicada species ( Cryptotympana atrata, Meimuna mongolica, and Platypleura kaempferi ) and tested the hypothesis that females have higher WLs than males possibly because they must carry the extra weight of eggs. There were significant dimorphic differences in body mass and WL for each of the three species. However, there were no significant dimorphic differences in total wing area for C. atrata and M. mongolica, whereas P. kaempferi females had larger mean total wing area than males. Among the three cicada species, males had lower WLs (and by inference, greater maneuverability) than females. In addition, the M vs. A scaling exponent (i.e., α) was numerically significantly greater than unity (i.e., α > 1). Thus, WL should scale with respect to M with α > 1, which accounts for why females have a larger WL than males. We interpret these results to indicate that gender dimorphism in body size and flight performance likely reflect selection on traits affecting reproductive success that, in turn, likely depend on flight maneuverability.